Fertilidad de Typic Dystrandepts of Costa Rica. II. Aniones (N, P, B, S, Mo), materia orgánica y textura - Bertsch, F; Cordero, A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The studied anions present similar nutritional characteristics in the nine Typic Dystrandepts of Costa Rica. P deficiency is the main lümiting problem, and in practice, the only one. P retention percent varies between 80 and 959% (additions of 225 600 Hg Pml to extract with Olsen modified solution three times the critical level of 12 H8/ml) The soils from the Cordillera de Guanacaste present the highest P retension values. When no P was applied, yields were statistically equal to the test plot even when all other elements were added. Every soil responded significantly to Pin direct relation to natural fertility The N supply derived from the mineralization of high organic matter content (48-24.4%) is not a limiting factor. In the greenhouse, in these soils, it is preferable to promote mineralization by applying P instead of adding additional N. Under laboratory conditions, B and S retention occurs at 85-96% and Sat 70-91% (16-15.6 HS B/ml and 84-264 Hg S/mi in extracts with CaHa (P03)a solution three times the corresponding critical level) Mo response only appeared in a soil of the Cordillera de Guanacaste. P concentration in Typic Dystrandepts of Costa Rica varies, with a 90% statistical probability, between 1 and 3 ug/ml, B, between 0.06 and 0.56 g/ml and S, between 7 and 29 HEml The texture of nine soils tends to be loam. P concentration in foliar tissue of sorghum grown in the greenhouse on these soils varies from 0.06 to 0.09%.